Issues of source studies in Khorezm People's Soviet Republic history - Bakhtigul Abdupattaevna Mamadaminova (Research Parks Publishing LLC, 2021)
This article analyzes Polvonniyoz Khoji Yusupov memoirs (1861 - 1936), the founder of the Young Khivans Party in Khorezm People's Soviet Republic and the first chairman of the Council of Ministers of Khorezm People's Soviet Republic. On the basis of his diaries, the historical events that took place in Khorezm and Turkestan between 1910 and 1924 are described in a unique style in Khorezm dialect of Uzbek language. P. Yusupov's memoirs are mainly devoted to the democratic Young Khivans Party activity, its work to overthrow the khanate in Khiva, to establish and strengthen an independent people's republic in Khorezm